Academic development and its practitioners : a view from the inside - Young, G. (African Sun Media, 2022)
The chapters in this collection are reflections of the intellectual, emotional and day-to-day experiences of professional staff engaged in academic development. They provide the reader with glimpses of how academic developers at one South African university are continuously shaping their identities through sense-making processes, how they creatively apply different theoretical approaches to both analysing and informing their work and what their views are of the practical and systemic challenges facing higher education. As such this book expands on as well as challenges the dominant ways of thinking about academic development and academic developers in higher education.